2002
DOI: 10.1007/3-540-47952-x_31
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of Open Student Models on Learning

Abstract: Abstract:In previous work [10], we reported on an experiment performed in the context of SQL-Tutor, in which we analysed students' self-assessment skills. This preliminary study revealed that more able students were better in assessing their knowledge. Here we report on a new study performed on the same system. This time, we analysed the effect of an open student model on students' learning and self-assessment skills. Although we have not seen any significant difference in the post-test scores of the control a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
117
1
9

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(132 citation statements)
references
References 13 publications
5
117
1
9
Order By: Relevance
“…One stream focuses on visualizing the model to support students' self-reflection and planning; the other one encourages students to participate in the modeling process, such as engaging students through negotiation or collaboration on the construction of the model [2]. Representations of the student model vary from displaying high-level summaries (such as skill meters) to complex concept maps or Bayesian networks.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…One stream focuses on visualizing the model to support students' self-reflection and planning; the other one encourages students to participate in the modeling process, such as engaging students through negotiation or collaboration on the construction of the model [2]. Representations of the student model vary from displaying high-level summaries (such as skill meters) to complex concept maps or Bayesian networks.…”
Section: Related Workmentioning
confidence: 99%
“…One popular solution to address the issue of control is the so-called open student modeling, an approach that permits the students to observe and reflect on their progress. In particular, visual approaches for open student modeling were explored to provide students with an easy-to-grasp and holistic view of their progress [1][2][3]. However, most of the open student modeling research focuses on the representation of an individual student --ignoring the social aspect of learning.…”
Section: Introductionmentioning
confidence: 99%
“…The next set of rows (numbered 1 through 10), identify the dimensions of openness, that allow the system's purpose for openness to be achieved. (Papanikolaou et al, 2003;Weber, Brusilovsky, 2001;Mitrovic & Martin, 2002). For example, ELM-ART (see Figure 2.9) used a partly filled in horizontal bar to indicate the percentage of learnt material.…”
Section: Openness In Adaptive Systemsmentioning
confidence: 99%
“…However, it has been shown that opening up the student model to the student, so that they could view "what the system thinks of them" is conducive to learning. In fact, the Open Student Model (OSM) plays quite a large role in increasing their metacognitive skills, which in turn helps their long-term learning [2,11]. Opening up the student model means that ITS authors have to consider how to best visualise this data so that the student can understand and make use of it.…”
Section: Introductionmentioning
confidence: 99%
“…Other types of OSMs include a tree structure [7,11], and concept graphs [5]. Most of these models are dynamic; others can be interactive; such as the negotiable student model [15].…”
Section: Introductionmentioning
confidence: 99%